ANALISIS EFISIENSI, KUALITAS ASET DAN STABILITAS BANK PEMBANGUNAN DAERAH SEBELUM DAN SESUDAH KONVERSI MENJADI BANK SYARIAH - IKARDI, IKARDI; SERLY, VANICA (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
This study aims to compare the efficiency, asset quality and stability of regional development bank before and after conversion to Islamic banks. This research is classified as a comparative descrictive research. The population of this study is Islamic commercial banks in Indonesia.The type of data used is secondary data obtained from financial reports uploaded on each bank's website and the OJK website. The sampling method is Purposive Sampling with quarterly reports of Aceh Bank and NTB Bank, each 15 before conversion and 15 after conversion, so a total of 30 samples before and 30 samples after. Efficiency variables use the ratio of CIR (Cost Income Ratio), Quality with APB (Problematic Earning Assets) and Stability with EAR (Equity to Asset Ratio). Testing data analysis using Paired T test, while the normality test using Shapiro-Wilk and Wilcoxon. Based on the results of the analysis and testing, it can be concluded that there are insignificant differences in the efficiency and quality of assets but there are significant differences in stability. The efficiency of the bank before conversion is higher than after but the asset quality and stability of the bank after conversion is highe